Report on industrial attachment with DSO National Laboratories - Long, Say Huan. (2008)
There are two important objectives behind the project. The first objective is to have a prototype application that can showcase the capabilities and benefits of a wireless sensor network application to potential clients. The second is to examine the issues, problems, and challenges in implementing a wireless sensor network application.